Kualitas Fisik Silase Rumput Gajah (Pennisetum purpureum Schumach) Dengan Penambahan Daun Kelor (Moringa oleifera): Physical Quality of Elephant Grass (Pennisetum purpureum Schumach) Silage with the Addition of Moringa Leaf (Moringa oleifera) - Dianita, Rahmi; Susilawati, Ayu; Sy, A. Rahman; Yani , Ahmad (Fakultas Peternakan Universitas Jambi, 2025)
Background: Preserving low-quality forage as silage by adding high-quality forage, such as from legume groups, can create good-quality feed while maintaining forage availability. Purpose: This study aimed to determine the physical quality of elephant grass (Pennisetum purpureum Schumach) silage by adding Moringa oleifera leaves. Methods: The research was arranged in a completely randomised design (CRD) with 4 treatments and 5 replications. The treatments were as follows: P0 = elephant grass (100%) without moringa leaves (control), P1 = elephant grass (95%) + moringa leaves (5%), P2 = elephant grass (90%) + moringa leaves (10%), P3 = elephant grass (85%) + moringa leaves (15%). Results: Adding moringa leaves to the elephant grass silage did not significantly affect the silage's colour, aroma, texture, presence of fungi, or moisture content (P>0.05). However, it had a significant effect (P <0.05) on the percentage of shrinkage, final weight of silage, and dry matter. Conclusion: Elephant grass silage with the addition of 10% moringa leaves, showed the best physical characteristics regarding shrinkage and dry weight. Overall, elephant grass silage with the addition of moringa leaves exhibited good colour, aroma, and texture, with a tolerable presence of mould.